Systematic review of differential inorganic arsenic exposure in minority, low-income, and indigenous populations in the United States. (July 2016) - Joca, Lauren; Sacks, Jason D.; Moore, Danielle; Lee, Janice S.; Sams, Reeder; Cowden, John
Abstract: Inorganic arsenic (iAs) is a human carcinogen and associated with cardiovascular, respiratory, and skin diseases. Natural and anthropogenic sources contribute to low concentrations of iAs in water, food, soil, and air. Differential exposure to environmental hazards in minority, indigenous, and low income populations is considered an environmental justice (EJ) concern, yet it is unclear if higher iAs exposure occurs in these populations. A systematic review was conducted to evaluate evidence for differential iAs exposure in the United States (US). The peer-reviewed literature was searched for studies that (1) estimated iAs exposure based on environmental concentrations of iAs in water, food, soil, or iAs biomarkers and (2) examined iAs exposure in minority, indigenous, and low income US populations. Five studies were identified that estimated exposures and provided demographic information about EJ populations. These studies reported arsenic concentrations in water, soil, or food to estimate exposure, with varied evidence of differential exposure. Additionally, six studies were identified that suggested potential arsenic exposure from environmental sources including soil, rice, private well-water, and fish, but did not report data stratified by demographic information. Evidence across these 11 studies was qualitatively integrated to draw conclusions about differential iAs exposure. The total body of evidence is limited by lack of individual exposure measures, lack of iAs concentration data, and insufficient comparative demographic data. Based upon these data gaps, there is inadequate evidence to conclude whether differential exposure to iAs is an EJ concern in the US. Highlights: Systematic review of differential inorganic arsenic exposure in US populations Limited number of studies identified using a priori search terms Inorganic arsenic exposure characterization is limitation of the data. Insufficient comparative demographics is another limitation of the database. Data are inadequate to make determination on potential differential exposures.